Spread of African cassava mosaic virus from cassava (Manihot esculenta Crantz) to physic nut (Jatropha curcas L.) in Ghana - Appiah, A S; Amoatey, H M; Klu, G Y. P; Afful, N T; Azu, E; Owusu, G K (Journal of Phytology, 2012)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> Investigations were made on the susceptibility of physic nut (Jatropha curcas L.) to African cassava mosaic virus (ACMV) and its possible role as an alternative host of the virus in Ghana. Ten J. curcas accessions in a field trial were interplanted with ACMV-infected cassava (Manihot esculenta Crantz) and left to natural spread of the virus from the cassava to the J. curcas plants for a period of 12 months. Populations of the whitefly vector, Bemisia tabaci (Gennadius) and the incidence of African cassava mosaic disease (ACMD) were monitored during the period. The J. curcas plants had low whitefly numbers, both in the wet (September â€“ October, 2008) season and in the dry (January â€“ February, 2009) season. By the end of the experimental period, 37.7% of the 120 J. curcas plants tested in all the accessions were found to be infected by ACMV, as assessed by symptom expression, double antibody-sandwich (DAS) ELISA or sap inoculation to Nicotiana benthamiana indicator plants. There were wide variations within and between the J. curcas accessions in their response to ACMV infection. This work is the first report of the natural infection of J. curcas by ACMV.